Amputations in the burn unit: A retrospective analysis of 82 patients across 12 years. Issue 7 (November 2017) - Li, Quan; Wang, Ling-Feng; Chen, Qiang; Wang, Shu-Jie; Li, Fang; Ba, Te
Highlights: Inexperienced young labor force represented the largest component among amputees. The amputation-related injuries occurred most commonly at the work place (62.2%). Electrical burn was the major mechanism of injury among amputees. Interdisciplinary communication would reduce the amputation rate. Abstract: Background: The aim of this study is to analyze the data of amputees in the burn center of the Inner Mongolia region and to provide instructive suggestions for a preventative reduction of the amputation rate. Methods: Between 2004 and 2016, all patient medical profiles were reviewed to extract data of patients with major amputation. Demographic data, mechanism of injury, location and level of amputation were recorded. The healing condition of the residual limb was noted. In addition, we performed comparisons of amputees whose injuries were caused by electricity and those whose injuries were related to other mechanisms. Results: Among the 82 amputees in our study, about 89% of amputees were male patients and the predominant age-group was 20–29 years (26.8%). The injuries occurred most commonly at the work place (62.2%) with laborers (40.2%) being the most commonly affected. The most common mechanisms of injury were electricity (51.2%) and hot crush (14.6%), followed by frostbite (13.4%). The most common level of amputation was the right wrist joint (n = 16). About 60.4% of the amputation sites were by primary healing. The rate of escharotomy in electrical burn amputees (n = 27, 62.3%) was significantly higher than the other groups (n = 16, 40.0%, p < 0.05). The first amputation in electrical burn group (7.2 ± 5.6) was significantly earlier than the other etiology group (17.9 ± 13.7, p < 0.05). Conclusions: Electrical burns were the major mechanism of injury among amputees. Effective safety measures, factory modifications, and adequate instructions should be implemented to protect laborers. Urgent interdisciplinary communication should be taken into account for the prevention reduction of the amputation rate in our region.